2007
DOI: 10.1128/cvi.00074-07
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Analogs Improve Efficacy of Acellular Pertussis Vaccine and Reduce Type I Hypersensitivity in Mice

Abstract: Pertussis is an infectious disease of the respiratory tract that is caused by the gram-negative bacterium Bordetella pertussis. Although acellular pertussis (aP) vaccines are safe, they are not fully effective and thus require improvement. In contrast to whole-cell pertussis (wP) vaccines, aP vaccines do not contain lipopolysaccharide (LPS). Monophosphoryl lipid A (MPL) and Neisseria meningitidis LpxL2 LPS have been shown to display immune-stimulating activity while exerting little endotoxin activity. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
3
24
0
2
Order By: Relevance
“…First, test the addition of MPL to DTaP and Tdap vaccines. Just one group appears to have tested a generic form of MPL as an additive for DTaP, reporting in 2007 that it improved efficacy, but only in mice and durability was not assessed [68]. Next, advance our understanding of the extent to which transient vaccine side effects are associated with desired immunization outcomes in vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…First, test the addition of MPL to DTaP and Tdap vaccines. Just one group appears to have tested a generic form of MPL as an additive for DTaP, reporting in 2007 that it improved efficacy, but only in mice and durability was not assessed [68]. Next, advance our understanding of the extent to which transient vaccine side effects are associated with desired immunization outcomes in vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ⌬lpxL2 NOMV vaccine contained only one-sixth as much LPS as the penta-acyl NOMV vaccine, one might have expected to see a greater difference between the LPSs in the ⌬lpxL2 NOMV and the ⌬lpxL1 NOMV vaccines. Other studies involving tetra-acyl LPS or lipid A and lipid A-like molecules have indicated that these molecules appear to be nonpyrogenic or antipyrogenic (14,15,28). Investigators have previously demonstrated that the lipid A from neisserial ⌬lpxL1 and ⌬lpxL2 mutants binds to human MD-2 and TLR4 because they have been used as competitive inhibitors of hexa-acyl lipid A (2,40,42).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing number of LPS-related molecules are being investigated for use for the treatment of sepsis (20) or for use as vaccines or vaccine adjuvants (13,14,30). One group of vaccine candidates that includes LPS as a major component is based on native outer membrane vesicles (NOMVs) from group B N. meningitidis.…”
mentioning
confidence: 99%
“…However, further investigations showed that both LPS derivatives are antagonists of human TLR4 (hTLR4) [124] and therefore are inadequate as adjuvant for humans, in contrast to mice. In spite of this disappointment as potential adjuvant molecules, genetically detoxified LpxL2 and LpxL1 LPS reduce the toxicity of native OMVs preparations in N. meningitidis [125] and whole-cell B. pertussis vaccines [126] and therefore they have been currently proposed to solve the unacceptable side effects of OMVs-based vaccines generated by LPS [66]. However, due to these molecules are hTLR4 antagonists, one could expect negative effects after activation of the immune system.…”
Section: Alteration Of the Lps Biogenesismentioning
confidence: 98%